2011
DOI: 10.1021/nl203964z
|View full text |Cite
|
Sign up to set email alerts
|

Crumpled Nanopaper from Graphene Oxide

Abstract: Graphene oxide (GO) in aqueous solution was aerosolized and rapidly dried to produce crumpled nanopaper-like sheets. Online size selection and aerosol mass analysis was used to determine the fractal dimension (D) of crumpled GO nanosheets as 2.54 ± 0.04. That is identical to macroscale materials, such as crumpled balls of paper and foil. Thermal reduction of crumpled GO nanosheets did not change D, even after loss of nearly 25% of the nanosheets mass. We demonstrate that D is able to be tuned by altering solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
200
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(214 citation statements)
references
References 16 publications
13
200
0
1
Order By: Relevance
“…Despite interesting theoretical progress [70,71], the existence of a crumpled phase with self-avoidance remains unclear at the present time [32,40]. We note that crumpled objects with fractional dimensions can be obtained experimentally by rapidly evaporating a solution containing graphene oxide membranes [72]. Remarkably, the measured fractal dimension D f ≈ 2.5-2.7 is in good agreement with the Flory-type argument, but one should note that such balls may be out of equilibrium and dominated by sticky van der Waals attractions.…”
Section: Introductionmentioning
confidence: 93%
“…Despite interesting theoretical progress [70,71], the existence of a crumpled phase with self-avoidance remains unclear at the present time [32,40]. We note that crumpled objects with fractional dimensions can be obtained experimentally by rapidly evaporating a solution containing graphene oxide membranes [72]. Remarkably, the measured fractal dimension D f ≈ 2.5-2.7 is in good agreement with the Flory-type argument, but one should note that such balls may be out of equilibrium and dominated by sticky van der Waals attractions.…”
Section: Introductionmentioning
confidence: 93%
“…For example, submicrometer-size ball-like crumpled graphene structures can be produced by isotropic compression and thermal reduction of GO [202]. Ma et al [203] also reported the fabrication of few hundred nanometer-size crumped graphene ball by rapid drying of GO. Unlike wrinkled graphene that experiences deformation by uniaxial confining forces, crumpled graphene undergoes multidirectional compression.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…GO exhibits a rough surface showing wrinkles 41,42 . It has been reported that during the drying process of GO, water exerts surface tension due to high affinity to GO oxidized domains 43 , inducing stresses during evaporation 44 , which force the soft sheets to fold and wrinkle 45,46 and/or can exacerbate the wrinkled structure 43 . In particular, in Figures 1E and 1F nanosheets edges of about 5 nm can be detected that correspond to the largest thickness observed in the sample.…”
Section: Go Characterizationmentioning
confidence: 99%